A Redox‐Active Binder for Electrochemical Capacitor Electrodes. Issue 17 (21st March 2016) - Benoit, Corentin; Demeter, Dora; Bélanger, Daniel; Cougnon, Charles
Abstract: A promising strategy for increasing the performance of supercapacitors is proposed. Until now, a popular strategy for increasing the specific capacity of the electrode consists of grafting redox molecules onto a high surface area carbon structure to add a faradaic contribution to the charge storage. Unfortunately, the grafting of molecules to the carbon surface leads to a dramatic decrease of the electrochemical performances of the composite material. Herein, we used the organic binder as an active material in the charge/discharge process. Redox molecules were attached onto its polymeric skeleton to obtain a redox binder with the dual functionalities of both the binder and the active material. In this way, the electrochemical performance was improved without detrimentally affecting the properties of the porous carbon. Results showed that the use of a redox binder is promising for enhancing both energy and power densities. Abstract : The Binder Age : The organic binder in hybrid materials was used as a platform for grafting to preserve the high double‐layer capacitance and the low ionic resistance of porous carbons. This binder allowed minimizing the loading of inactive material in the electrode, while improving its capacitance and reducing its ionic resistance, mainly owing to a better wettability of the porous carbon.